2013
DOI: 10.3390/molecules181215000
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Activity of 3-[Phenyl(1,3-thiazol-2-yl)-amino]propanoic Acids and Their Derivatives

Abstract: New N,N-disubstituted β-amino acids and their derivatives with thiazole, aromatic, and heterocyclic substituents were synthesized from N-phenyl-N-thiocarbamoyl-β-alanine by the Hantzsch method; derivatives with hydrazone fragments were also obtained. Some of the synthesized compounds exhibited discrete antimicrobial activity, and 3-[(4-oxo-4,5-dihydro-1,3-thiazol-2-yl)(phenyl)amino]propanoic acid was found to promote rapeseed growth and to increase seed yield and oil content.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…Pyrrolidinone derivatives are widely known for their biological activities such as antimicrobial [1], antiviral [2], etc. Furthermore, thiazole is an important pharmacophore associated with varied biological activities including antimicrobial [3], antiviral [4]. In the view of this interesting pharmacological content we have decided to design and synthesize the molecular framework of new pyrrolidinone derivatives with heterocyclic or acyclic fragments and investigate their antibacterial activity.…”
Section: Introductionmentioning
confidence: 99%
“…Pyrrolidinone derivatives are widely known for their biological activities such as antimicrobial [1], antiviral [2], etc. Furthermore, thiazole is an important pharmacophore associated with varied biological activities including antimicrobial [3], antiviral [4]. In the view of this interesting pharmacological content we have decided to design and synthesize the molecular framework of new pyrrolidinone derivatives with heterocyclic or acyclic fragments and investigate their antibacterial activity.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous paper, 24 a synthesis of Nphenyl-N-carboxyethylaminothiazoles with antibacterial properties was reported. Also, it was found that 3-[(4-oxo-4,5-dihydro-1,3-thiazol-2-yl)(phenyl)amino]propanoic acid promotes rapeseed growth, increases seed yield and oil content.…”
Section: 23mentioning
confidence: 99%
“…The precipitate was filtered off, washed with water, dried to give 22 as a white solid, yield 88%, 1.37 g, mp 155-156 C (from methanol); IR (ν max , cm [24][25][26][27][28]. A round-bottomed flask equipped with a magnetic stirring bar was charged with a cooled solution of the corresponding aromatic aldehyde (5 mmol) in aqueous 10% NaOH (5 mL), and the compound 23 (1.61 g, 5 mmol) solution in methanol (20 mL) was added dropwise.…”
Section: N-(4-fluorophenyl)-n-(4-phenylthiazol-2-yl)acetamide (22)mentioning
confidence: 99%
“…Hydrazone derivatives of heteroaromatic compounds have also been reported to possess anti-inflammatory 24,25 , anticancer 26 , antitumor 27 , antibacterial or plant-growth activity 28,29 .…”
Section: Introductionmentioning
confidence: 99%